Effect of Nonspecific Chronic Low Back Pain on Walking Economy: An Observational Study. Issue 3 (3rd May 2016) - Carvalho, Alberito Rodrigo; Ribeiro Bertor, Welds Rodrigo; Briani, Ronaldo Valdir; Zanini, Gabriela Matté; Silva, Lígia Inez; Andrade, Alexandro; Peyré-Tartaruga, Leonardo Alexandre
ABSTRACT: The authors investigated the effects of chronic low back pain (LBP) and walking speed (WS) on metabolic power and cost of transport (CT). Subjects with chronic nonspecific LBP (LBP group [LG]; n = 9) and healthy (control group [CG]; n = 9) were included. The test battery was divided into 3 blocks according to WS as follows: preferred self-selected speed (PS), and lower and higher than the PS. In each block, the volunteers walked 5 min, during which oxygen consumption was measured. Although without differences between groups, the LG had CT lower in slower speeds than in faster speeds. Walking speed affected CT only in the LG, which the group had the greatest walking economy at slower speeds.